2020
DOI: 10.1002/jia2.25647
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for reduction of HIV‐related stigma: a model derived from longitudinal qualitative research in Kenya and Uganda

Abstract: Introduction The rollout of antiretroviral therapy (ART) has been associated with reductions in HIV‐related stigma, but pathways through which this reduction occurs are poorly understood. In the newer context of universal test and treat (UTT) interventions, where rapid diffusion of ART uptake takes place, there is an opportunity to understand the processes through which HIV‐related stigma can decline, and how UTT strategies may precipitate more rapid and widespread changes in stigma. This qualitative study sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Finally, this study relied on cross-sectional analysis of baseline data and therefore did not explore changes in forms of stigma in these communities over time. Recent research in the study setting involving analysis of data collected at multiple time points has suggested changes in stigma did occur, suggesting pathways through which stigma can decline in the context of rapid uptake of HIV testing and treatment [33,56].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study relied on cross-sectional analysis of baseline data and therefore did not explore changes in forms of stigma in these communities over time. Recent research in the study setting involving analysis of data collected at multiple time points has suggested changes in stigma did occur, suggesting pathways through which stigma can decline in the context of rapid uptake of HIV testing and treatment [33,56].…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of stigma has been noted by several other authors and remains a challenge for any HIV program [ 75 , 76 ]. However, it should be recognized that the scaling up of HIV prevention and treatment services, especially in a universal ‘test and treat’ approach, could help reduce HIV-related stigma in the community through several pathways and improve access to these services [ 77 , 78 ]. We also found strong evidence of higher odds of HIV testing among the most educated women, consistent with other studies on youth in the SSA region [ 21 , 33 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Words also matter and consistent use of terms like 'people who have asthma' rather than asthma 'victims' or CRD 'sufferers' can start to shift mindsets. There are many transferable lessons to be learned from community de-stigmatisation efforts with HIV in the antiretroviral therapy era (25) and, more recently, efforts being applied to COVID-19 related stigma (26).…”
Section: Discussionmentioning
confidence: 99%